KEUNGGULAN SEKOLAH DASAR PLUS AL GHIFARI MELALUI PENDEKATAN ANALISIS SWOT - junaedi, Jujun; Purwanda, Eka (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
This research aims to find out appropriate strategies for improving excellence at Al Ghifari Islamic Elementary School, It is an elementary school that combines the government curriculum with the foundation curriculum. In this school, students are not only taught general lessons like in state elementary schools, but they are also taught religious lessons with a fairly balanced number of subjects. This research also uses a SWOT analysis approach to determine its strategy. At the data collection stage,. Primary data is in the form of observations to see directly the conditions, atmosphere, reality that occur at school. Based on the results of the SWOT analysis, there are several advantages that can be highlighted at SD Plus Al Ghifari and suggestions that can be made are efforts to develop teaching staff, improve facilities and infrastructure, promote excellence, coordinate with parents, and maintain balance in education are crucial steps. to create an optimal learning environment in Islamic Primary Schools. With the hope that through the implementation of a strategy for developing educators in line with the school's objectives, it can also create an educational institution that not only meets quality standards but is also capable of making a significant positive impact on the development of students